Sink node mobility for ellipsoidal area coverage for efficient data collection in Wireless Sensor Networks. (4th August 2008) - Kamat, Maznah; Ismail, Abd Samad; Olariu, Stephan
In this article, we explore the usage of Hilbert space filling curves in solving area covering for a target field, and also ensuring accurate gathering of periodic data collection. In covering the area, the mobility pattern that is based on modified Hilbert space filling curves suited best for ellipsoidal bounded area of interest. Comparative study demonstrates those circular and conventional Hilbert traversals are rejected due to non-adaptiveness to monitoring area shapes.